Reconstructing Teacher–Student Relations in Islamic Adab Education: A Critical Analysis of the Islamic Religious Education Curriculum in Madrasah Aliyah - Lu'lu'ah Luthfiyah Hamda; Ayus Ahmad Yusuf; Abdul Aziz (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to reconstruct teacher–student relations in Islamic adab education by critically examining the construction of authority, obedience, and student positioning within the Islamic Religious Education curriculum of Madrasah Aliyah. The study employed a qualitative library research design integrating thematic synthesis, critical textual analysis, Jacques Derrida’s deconstruction, and Michel Foucault’s theory of power relations. Data were collected from PAI curriculum documents, adab-related learning materials, classical Islamic educational texts, and relevant Scopus-indexed literature. The findings reveal three interconnected themes: teacher authority remains a fundamental element of Islamic adab education, student agency is increasingly recognized as an essential dimension of meaningful learning, and safe learning environments require a balance between ethical authority, learner participation, and educational accountability. The study further demonstrates that hierarchical interpretations of authority and obedience can be reinterpreted through a dialogical-adab framework that promotes mutual respect, learner dignity, and educational responsibility. The novelty of this study lies in integrating Islamic adab traditions, student agency theory, educational safeguarding, and critical perspectives on power relations into a unified framework for curriculum reconstruction. The study contributes to Islamic educational theory and curriculum development by offering a dialogical-adab model that supports ethical leadership, student empowerment, and safe learning environments in contemporary Islamic education.